ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN (Studi Kasus Pada CV. Kaka Bersaudari Pangkalpinang) - Toybatulillah, Rizki; Ruben Manullang, Rizal; Medinal (Jurnal Progresif Manajemen Bisnis, 2018)
This is an undergraduate thesis is written and compiled by Rizki Toybatulillah (student id 230140010). The thesis entitled in Bahasa Indonesia; “Analisis Gaya Kepemimpinan dan Budaya Organisasi terhadap Kinerja Karyawan Pada CV. Kaka Bersaudari”. It consists of (the total pages from chapters 1 through 6 are 98 sheets) pages and was administrated in the city of Pangkalpinang. The research was conducted by April 2018 through June 2018. The purpose of this study is to determine the effect of Leadership style, Organizational Culture towards the Employee Performance, by partially and simultaneously at commmanditaire vennootschaap(c.v) Kaka Bersaudari, Pangkalpinang. Based on the results of the study shows that: (1) there is a significant influence between Leadership style towards Employee Performance, which is approved by the value of t-countmuch greater t-hant t-table(3.402> 2.012). (2) The results also show that there is a significant influence between Organizational Culture towards Employee Performance, which is proven by the value of t-count much greater than the t-table (2.393> 2.012). (3) The results show that there is a significant influence between Leadership Style and Organizational Culture simultantenously towards Employee Performance by the means of empirically finding by the value of F-count much greater than Ftable (3.276>3.20). In conclusion, according to the result of this study, we suggested to the commanditaire vennootschaap (c.v) Kaka Bersaudari, Pangkalpinang management consider the improvement on their leadership capability in order creates the organizational cultural by objectives and profesional, because it was proven empirically has a contributioan towards the employee performance. The Management studies shown; as long as the employee able to perform well by doing their responsibility and tasks, it will generates the positive value to the commmanditaire vennootschaapit self.